An overview in implement green logistics: a case study at Kontena Nasional Berhad (Kuantan branch) / Wan Ahmad Muzamir Wan Abd Manan - Wan Abd Manan, Wan Ahmad Muzamir (2016)
Green logistics is one of the environmental friendly terms that relates with producing, supplying, and moving goods in a sustainable manner. The impact of practicing green logistics is not only towards the environment itself but also indirectly give impact towards the society and business. Today, many developed countries have put great efforts towards practicing green logistics to obtain benefits and there are claims that green logistics can be an effective tool and strategy to increase competitive advantage for business survival. Therefore, the objectives of this study are to understand the green logistics practised at Kontena Nasional (KN) Kuantan and to explore the implementation of green logistics to KN operations. The results of this study were obtained through face-to-face interview with 8 respondents who are decision makers, implementers and users at KN Kuantan. The data was analyzed using the Textual analysis, later compared to the literatures about green logistics and environment pollution. The knowledge of green logistics, benefit of green logistics, green logistics activities, green logistics activity (company focus), and impact of implementation & not implementation green logistics are a part of the findings. The result from this study is expected to assist the researcher in deriving a better understanding of the green logistics activities that are undertaken by KN Kuantan and how these activities are being dealt with in their operation. This study also revealed economic and environment aspects are positively significant with level of green logistics activities.